PEMBENTUKAN PORTOFOLIO OPTIMAL PADA SAHAM-SAHAM INDEKS IDX30 DI PT BURSA EFEK INDONESIA - Sudarsana, I Made Budi; Sedana, Ida Bagus Panji; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.N0.02.TAHUN 2014, 2014)
Increasing public awareness and advances in information technology has been advancing the Indonesian capital market as an alternative investment. Investing in the stock market can be done by forming portfolios Markowitz Model and can use the strategy of stock selection based on price earnings to growth ratio. This study aims to determine the composition of the stocks forming the optimal portfolio and the proportion of funds invested. Shares used the stock index IDX30 period August 2013-January 2014, and then taken 15 stocks with price earnings to growth ratio is the lowest positive and analyzed using Microsoft Office Excel 2007. Results showed that the optimal portfolio shares forming Adaro Energy Tbk. (ADRO) of 16.42%, Aneka Tambang Tbk. (ANTM) of 5.00%, Jasa Marga (Persero) Tbk. (JSMR) of 34.11%, Perusahaan Gas Negara Tbk. (PGAS) of 27.47%, and Pakuwon Jati Tbk. (PWON) of 17.01%. Future studies may use other portfolio pricing models. Keywords: portfolio, price earnings to growth ratio, markowitz models